Do influence at work and possibilities for development mitigate the impact of job demands for workers with and without depression - Patricia Ots; Anita C Keller; Eva Altrock; Sander KR van Zon; Sandra Brouwer (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: Jobs characterized by low job demands and high job resources are associated with better work outcomes, yet it remains unclear whether this is the case for workers with depression. This study examined whether depression moderates the relationship between job demands, job resources, and maintaining employment. METHODS: Data from the longitudinal population-based Lifelines cohort study were matched with register data on employment from Statistics Netherlands (N=55 950). Job demands included quantitative demands and work pace; job resources included influence at work and possibilities for development. The two-way interaction between job demands and depression and the three-way interaction between job demands, job resources and depression were examined in a zero-inflated Poisson regression model with path 1, including a binary employment outcome, and path 2, a count variable including months out of employment. RESULTS: The interaction effect of job demands and depression on being employed was significant [b=-0.22, 95% confidence interval (CI) -0.44‒0.01]. Workers without depression were more likely to be employed whereas workers with depression were less likely to be employed if they had high job demands. The three-way interaction between job demands, job resources, and depression was significant for months out of employment (b=0.15, 95% CI 0.01‒0.29), indicating that workers with depression had more months out of employment when reporting high job demands and high job resources compared to workers without depression. Discussion Although increasing influence at work and possibilities for development to prevent negative work outcomes may be beneficial for workers without depression, this approach might be limited for workers with depression.